Microstructure imaging with diffusion MRI and microscopy - Howard, A (2020)
Diffusion MRI is a powerful, non-invasive tool for microstructure imaging because of its sensitivity to structures on the microscopic scale. By analysing the diffusion signal we can infer the structural connectivity of the human brain or changes in the myelo- and cyto-architecture. This inference requires biophysical signal modelling, where we aim to map macroscopic diffusion signals onto biologically-meaningful tissue parameters. However, this mapping is often ill-posed, with multiple parameter sets fitting the signal equally well, and our parameters are said to be degenerate. Because degenerate parameters lack tissue specificity and are thus difficult to interpret, they present a serious challenge to diffusion modelling and limit the widespread application of diffusion MRI in both neuroscience research and clinical medicine.